MANAJEMEN PEMBELAJARAN SD NEGERI 117505 PANJANG TONGAH PADA PEMBELAJARAN DI MASA PANDEMI - Aprilia, Indah; Lubis, Joharis (Lingua, 2022)
The Covid-19 pandemic has disrupted the conventional learning process. So a solution is needed to answer this problem. Online learning is one alternative that can overcome this problem. This study aims to describe the management of online implementation at SD Negeri 117505 Panjang Tongah. This study identifies online learning management during the covid-19 pandemic and analyzes the policies of principals and teachers in their implementation. This research uses a qualitative approach in the form of a case study. The data collection procedure used: (1) semi-structured interview (Indept Interview), (2) participatory observation, (3) document study. Data analysis was carried out simultaneously with the data collection process. Checking the validity of the data includes four techniques, namely credibility, transferability, dependability, and confirmability. The results of this study indicate that 1) the implementation of online learning at SD Negeri 117505 Panjang Tongah takes place online through the class whatsapp group platform; 2) the obstacles that arise from online learning are the limitations of teachers controlling interests and students' learning motivation, limitations of parents in spending time and providing learning facilities and infrastructure, students prefer face-to-face learning, and obstacles in adapting technology